A poisoned apple: First insights into community assembly and networks of the fungal pathobiome of healthy-looking senescing leaves of temperate trees in mixed forest ecosystem - Tanunchai, Benjawan; Ji, Li; Schroeter, Simon Andreas; Wahdan, Sara Fareed Mohamed; Larpkern, Panadda; Lehnert, Ann-Sophie; Alves, Eliane Gomes; Gleixner, Gerd; Schulze, Ernst-Detlef; Noll, Matthias; Buscot, François; Purahong, Witoon (Frontiers in Plant Science, 2022)
Despite the abundance of observations of foliar pathogens, our knowledge is severely lacking regarding how the fungal pathobiome is structured and which processes determine community assembly. In this study, we addressed these questions by analysing the fungal pathobiome associated with the senescing leaves and needles of 12 temperate tree species. We compared fungal pathogen load in the senescing leaves and demonstrated that healthy-looking leaves are inhabited by diverse and distinct fungal pathogens. We detected 400 fungal pathogenic ASVs belonging to 130 genera. The pathogenic generalist, Mycosphaerella, was found to be the potential most significant contributor to foliar disease in seedlings. The analyses of assembly process and co-occurrence network showed that the fungal pathogenic communities in different tree types are mainly determined by stochastic processes. However, the homogenising dispersal highly contributes in broadleaf trees, whereas ecological drift plays an important role in conifer trees. The deterministic assembly processes (dominated by variable selection) contributed more in broadleaf trees as compared to coniferous trees. We found that pH and P levels significantly correspond with fungal pathogenic community compositions in both tree types. Our study provides the first insight and mechanistic understanding into the community assembly, networks, and complete taxonomy of the foliar fungal pathobiome in senescing leaves and needles.